Academic hope and self-regulation as predictors of creative thinking among undergraduate students - Ghbari, Thaer A.; Harahsheh, Ahmad H. (Creativity Studies, 2024)
Universities always strive to qualify students to be creative in their careers, so researchers in the creativity domain seeks the factors that affect creative thinking to understand this concept more deeply. As a result, the current study aimed at exploring the predictive power of self-regulation and academic hope in the creative thinking among undergraduate students. A total of 481 (249 males, 232 females) undergraduate students from different universities in Saudi Arabia participated in this quantitative correlational study, and completed the scale of self-regulation scale, the academic hope scale, and the creative thinking scale. The findings showed that the level of creative thinking of the undergraduate students was medium, but they have high levels of the academic hope and self-regulation. It was also found that self-regulation and academic hope were good predictors of creative thinking. It was recommended that educators and practitioners should consider academic hope and self-regulation if they want to foster creativity thinking.